Vulnerabilities of Syrian refugee children in Turkey and actions taken for prevention and management in terms of health and wellbeing - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Background: The Syrian crisis, which started in March 2011, has resulted in the displacement of 6.3 million refugees predominantly to neighboring countries in addition to the internal displacement of 6.2 million people. Turkey is the country hosting the largest number of refugees in the world with 3.6 million Syrian refugees 46 % of which are under 18 years old. Objective: The purpose of this article is to conduct a narrative review and analyze the vulnerabilities of refugee children in Turkey from the lens of the Sustainable Development Goals (SDG), more specifically SDG Goal 3: Good Health and Wellbeing, with a specific focus on Syrian refugee children. Moreover, this article explores the actions taken to prevent and mitigate issues that arise from these vulnerabilities. Method: This narrative review article collected data from various primary and secondary sources on the Turkish refugee framework including national and international legislation, governmental and non-governmental data and reports, and scientific papers. Results: Syrian refugee children in Turkey are facing a variety of risks in terms of their health and wellbeing including communicable and non-communicable diseases, post-traumatic stress disorder, depression, family violence, child labor, and child marriage. The measures taken for prevention and response by governmental and non-governmental entities are multilateral and aim to address issues from multiple perspectives including medical, psychosocial, child protection, and legal. Conclusions: The interventions and restructuring of the health system in Turkey contribute to the SDG number 3 for refugee children. The existence of a legal system which enables refugee access to health, protection, and other social services is key to achieve this goal. However, the existing system could be improved especially through solidifying the legal basis and centralizing the implementation for child and refugee protection. The engagement of all stakeholders to improve the health and wellbeing of refugee children remains vital.
Keywords: Syrian refugees; Turkey; Refugee children; Sustainable development goals; Child health; Wellbeing; POSTTRAUMATIC-STRESS-DISORDER; MENTAL-HEALTH; RISK; SANITATION; VIOLENCE; IMPACT; SAMPLE; WATER; WAR